South Caucasus and Central Asia - The Belt and Road Initiative : Georgia Country Case Study - World Bank (World Bank, Washington, DC, 2020)
Georgia is the only country in the CAC region that can access markets around the world through its own seaports and thus less dependent on China’s BRI overland corridors for trade, investment and growth. Nevertheless, the Georgian government is investing in the one BRI corridor China, Europe route that passes through the Caucuses, partly because it provides a faster route to China. The potential for larger volume of Chinese transit cargo on this route may also be attractive given its desire to become a major transit and trading hub in the region. With greater people-to-people contact between China and Georgia, there could also be greater access to China’s outward FDI under the BRI that would bring with it capital, better technology as well as managerial and marketing know-how. Chinese private firms are already investing in Tbilisi, Kutaisi and other areas in the country. Georgia’s liberal investment and trade regime, especially its free trade agreements with the European Union (EU), China, Turkey, and its location, make it eminently suited for such FDI inflows, including participation in China-centric Global Value Chains (GVCs). This note assesses the potential impact of BRI over connectivity and the Georgian economy. It looks at how, if fully implemented globally, the BRI is expected to achieve better transport connections and greater economic integration of participating BRI countries, discusses improvements in Georgia’s cross-border transport, electricity and ICT infrastructure to-date, and the potential impact of the completion of BRI transport projects on lowering Georgia’s shipment time. It further looks at the likely economic impact of BRI reductions in shipment time on exports, FDI and GDP, the within-country regional distribution of that impact and how complementary polices can enhance the positive impact, mitigate risks and reduce regional inequity. Finally, it also examines the fiscal risk of scaling-up investment in BRI projects in the coming years without undermining medium-term debt sustainability.